Challenges and opportunities: policy options for the forestry sector in the Asia-Pacific region - Byron, R.N. (Food and Agriculture Organization of the United Nations, 1997)
The major policy issues and opportunities confronting governments in the Asia-Pacific region in trying to achieve sustainable and equitable use and management of their forests are analysed. The paper identifies trends in the forestry sector, and their broader underlying economic, demographic and social causes, particularly in regard to who will manage which forests in the future, for what objectives. These forces include pressures for decentralisation, corporatisation, privatisation and devolution to local community groups, as part of widespread moves to smaller governments ‘who concentrate on steering the boat, rather than rowing it’. The paper emphasises the current social and economic significance of forests to the people who live in/near tropical forests in the Asia-Pacific region, and suggests possibilities for improving the social, economic and environmental conditions of forests and the people who live in/near them. Some development opportunities in the forestry sector are examined including the possible long-term trade-offs between economic, social and environmental objectives and needs. The potential for negotiating ‘win-win’ outcomes and options for policy and institutional reforms by national governments in the Asia Pacific region are examined, and how these might be reinforced by international efforts.